Curriculum for Undergraduate Medical Sciences: Traditional, Integrated or Both - Sadia Choudhury Shimmi; M. Tanveer Hossain Parash; Fairrul Masnah @ Kadir (Penerbit UMS, 2023)
The traditional curriculum for undergraduate medical students ensures discipline-based learning. In a traditional curriculum, students get ample time to get a detailed understanding and undergraduate-level knowledge which is elaborative and sufficient for each subject. Although the students gain ample knowledge of the subject, they lack in correlating the gained information with other subjects. This is not the students’ fault; instead, it is due to the lack of scope of correlation in the traditional curriculum. In this curriculum, students are not taught about the applicability of the gained information. Consequently, basic science or pre-clinical subjects seem irrelevant to the students as if the clinical subjects are independent of these subjects, whereas the reality is the opposite (Watmough et al., 2009). The knowledge of the basic subjects serves as the targeted goal of clinical manoeuvre. Traditional curriculum receives criticism for demotivating students to learn basic subjects to practice as a doctor. Moreover, the traditional curriculum is a more lecture-dependent one-way teaching method devoid of a student-oriented approach (Christianson et al., 2007). There is no scope for problem-solving or critical thinking rather than pedagogical learning. Another disadvantage of the traditional curriculum is that students need to wait until clinical years to have experience with patients. Therefore, there is no opportunity for clinical skill development earlier in this curriculum (Rahman, 2022).